ESR of Gd3+ and Er3+ in Pr2-xCexCuO4 - Martins, G. B.; Rao, D.; Valdivia, J. A.; Pires, M. A.; Barberis, G. E.; Rettori, C.; Venegas, P. A. [UNESP]; Oseroff, S.; Fisk, Z. (American Physical Society (APS), 1995)
Electron spin resonance (ESR) of Gd3+ and Er3+ in single crystals of Pr2-xCexCuO4 (0≤x≤0.15) at liquid-helium temperature shows crystal field (CF) effects corresponding to a C4v point symmetry. Upon doping with Ce4+, a reduction of about 23% in the second-order CF parameter b20 is found with no significant change for the other CF spin-Hamiltonian parameters. The resonance lines broaden and present a Dysonian line shape at higher Ce4+ concentration, which is consistent with an increase in the CF inhomogeneity and the metallic character of the compound. Magnetic-susceptibility measurements present a small increase in the low-temperature anisotropy upon doping, consistent with a smaller B02 crystal-field parameter for Pr3+ in Pr2-xCexCuO4. The reduction in the CF parameters is tentatively attributed to charge transfer from Ce atoms to the CuO2 planes. The exchange parameters jGd-Pr and jPr-Pr are estimated from the ESR and susceptibility measurements. © 1995 The American Physical Society.